Preparation of cattle manure compost using saw dust and rice straw - Ali, MM; Khan, FA; Hossain, MM; Rahman, ANMI (Bangladesh Journal of Animal Science, 2015)
The experiment was carried out to examine the possibilities of making compost by using cattle manure with saw dust and rice straw by three trials in each. The trials were conducted with cattle manure (T1), cattle manure with saw dust (T2) and cattle manure with rice straw (T3). There were three replications in each treatment. The sample from composted materials was collected at 0 and 60 days for proximate analysis. At 0 day, the highest dry matter (DM), organic matter (OM) and crude fiber (CF) were observed in T2. The highest crude protein (CP) and ash content were observed in T1 while the highest pH was observed in T3. The carbon nitrogen (C/N) ratio was the lowest in T1. At 60 days of composting cattle manure the highest DM, OM and CF were observed in T2 comparison with 0 day data. At 60 days of composting the highest CP and ash content were observed in T2 and the C/N ratio and pH were lowest in T1. Therefore, the use of saw dust and rice straw improves quality of cattle manure compost. It may be concluded that proximate composition of all samples at 60 days in T2 treatment was acceptable up to the end of composting period. However, T2 was more effective compare to other treatments at 60 days of composting in terms of DM, OM, CP, ash content and pH. So, it is recommended that farmers can practice cattle manure composting using saw dust up to 60 days of composting as organic fertilizer. DOI: http://dx.doi.org/10.3329/bjas.v44i1.23145 Bang. J. Anim. Sci. 2014. 44 (1): 64-68